Nature Through The Potential Development of Tourism to Increase Economic And Social Village Sepakung - romadhon, imam wahyu; Reza Pratiwi Prabandari; Monica Indah Damayanti; bayu pamungkas; Chandra Syahrul Indrasworo; Lusi Shentiya Lindi Yati; Muflichati Wanda Nur Aini (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2020)
Sepakung tourist village is a village that has a pretty good tourism potential and is a sector that spur the economy in Sub Banyubiru, excellence Sepakung the village is a tourist village that is still very beautiful area that makes a very natural tourism potential of local tourist interest. Sepakung travel planning in the village can spur other sectors such as transport, food stalls or souvenirs, and others so that the local governments will benefit in the areas associated with tourism. Sepakung tourist village located in the district Banyubiru, Semarang regency which has an opportunity to improve the life of village communities Sepakung, with the development of rural tourism is expected to make villagers sepakung to get a good progress of the economy, which notaben sepakung native village are farmers who have an average primary school education. But this can happen if the development and management of tourist villages sepakung can be done well. The method used is descriptive qualitative method. Respondents in this study included 302 respondents using as a reference parcel map data retrieval and two tours as a tour manager in the capture of data collection techniques include, observations, interviews, questionnaires, study the documentation. Data were analyzed using, percentage and SWOT analysis. The results showed that (1) Village tour sepakung did little to change people's livelihood Sepakung village. The majority of people work as farmers and laborers (2) Revenue community work in the village Sepakung average of less than one million rupiah (3) Development of a tourist village in Sepakung pretty good (4) The appeal in the village Sepakung to attract tourists is a tourist attraction (5) Measures for the development of tourist villages in Sepakung quite. The contribution made by local authorities make people more enthusiastic to develop the potential of the village